A Small Organic Molecular Catalyst with Efficient Electron Accumulation for Near‐unity CO2 Photoreduction. Issue 23 (13th October 2022) - Liu, Ting; Li, Yang; Fang, Youting; Fu, Yukang; Chen, Longxin; Chao, Duobin
Abstract: Molecular catalysis is of great interest to CO2 photoreduction. Various transition metal complexes have been developed as efficient molecular catalysts. However, it remains a challenge to catalyze CO2 reduction by a small organic molecular photocatalyst, as the accumulation of multiple electrons in a small organic molecule is normally difficult for CO2 reduction. We report herein a small organic molecular catalyst can be used for selective reduction of CO2 to CO under visible light irradiation. The turnover number (TON) of CO formation is found to be 400±26 with near 100% selectivity in DMF/H2 O medium. UV‐Vis absorption spectroscopy, density functional theory (DFT) calculations, and spectroelectrochemical studies demonstrate that the organic molecular catalyst is capable of accumulating electrons through a 2e − reduced product which shows good stability and is responsible for interacting with CO2 . These findings elucidate an accessible way to develop purely organic molecular catalysts for CO2 reduction by strengthening the electron accumulation. Abstract : A small organic pyridinium derivative of typical terpyridine has been found to be a highly selective molecular photocatalyst in CO2 photoreduction via the efficient electron accumulation in the conjugated molecular structure.